Response to experimental vaccination against newcastle disease in domestic ducks (Anas platyrhynchos): Clinical and immunological parameters - Paulillo, Antonio Carlos [UNESP]; Franzo, Vanessa Sobue; Schmidt, Elizabeth Moreira dos Santos [UNESP]; Doretto Junior, Luciano (My University, 2009)
Clinical and immunological aspects of vaccinated domestic ducks against Newcastle disease were evaluated. Forty-eight domestic ducks were distributed into four different experimental groups, vaccinated or not against Newcastle disease: G1 (Ulster 2C strain), G2 (B1 strain), G3 (LaSota strain) and G4 (not vaccinated-control). The immune response was evaluated by the HI test. Domestic ducks showed a moderated to elevated antibody response when vaccinated against Newcastle disease with Ulster 2C, B1 and LaSota strains and no clinical signs associated with post-vaccinal reactions were observed. © Asian Network for Scientific Information, 2009.
Keywords: Anas platyrhynchos; B1; Ducks; LaSota strains; Newcastle disease; Ulster 2C; Vaccination; Anas